Combustion of Low-Grade Fuel and Biomass in Pulsating Layer - I. Bokun (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents a model of fuel combustion in pulsating layer and demonstrates its advantages. Design of a burning device for combustion of low-grade fuel and biomass in pulsating layer has been proposed in the paper.